Pengaruh Lifestyle, Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Iphone Di Kota Malang (Studi Pengguna IPhone Di Kota Malang) - Noval Fadillah Putra; Pardiman Pardiman; Rahmawati Rahmawati (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research aimed to identify the effect of lifestyle, price, and product quality on iPhone purchasing decisions in Malang City. The independent variables used are lifestyle, price, and product quality, while the dependent variable is the purchase decision. The sample used in this study were 115 people in Malang city who used an iPhone. The data collected using a questionnaire. The analysis method using a instrument test, multiple linear regression analysis, classical assumption test R2, determination test, hypothesis testing using the help of SPSS 25.0 computer software. The results of this study indicate that Lifestyle has a positive and significant effect on purchasing decisions, price has a positive and significant effect on purchasing decisions, product quality has a positive and significant effect on purchasing decisions, and Lifestyle, Price, and Product Quality simultaneously have a positive and significant effect on the IPhone Purchase Decision variable in Malang City. Keyword: Lifestyle, Price, Product Quality, And Purchasing Decisions